Report of Seventh Plan Subgroup on Indigenisation for Petroleum Sector Equipment & Services - Planning Commission (Planning Commission, 1984)
During the meetings of the sub-group it was decided that in view of separate sub-group on R&D under the Working Group on Petroleum, discussions on technology imports should be within the purview of R&D subgroup. It was also agreed that special training needs (technical and managerial capabilities) should be left to the individual organisations to discuss in the Main Working Group on Petroleum. In view of these decisions sub-group was required to concentrate only on development of indigenous capacity for manufacture of equipment required for the Seventh Five Year Plan.
Equipment & Services
Equipment & Services